2019
DOI: 10.18844/gjflt.v9i3.4221
|View full text |Cite
|
Sign up to set email alerts
|

The effect of watching captioned TV series on speaking accuracy of Iranian advanced EFL learners

Abstract: The present study aimed to find out the effect of watching captioned TV series on speaking accuracy of Iranian advanced English as a Foreign Language (EFL) learner. To do so, 66 advanced learners were selected out of 104 ones, using Oxford Placement Test. The researchers assigned the participants randomly into three groups, one control and two experimental, each including 22 learners. One of the experimental groups watched the series with English subtitles and the other group with Persian subtitles while the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…For example, the English curriculum of 2 nd , 3 rd and 4 th grades of the primary schools is based on listening and speaking skills for which the use of technology is required; some of the teachers may have difficulty in terms of using technology. Technology is very effective in language learning (Uzunboylu & Ozcinar, 2009;Ceker & Keser, 2019;Tavoosy & Jelveh, 2019;Tajgozari, 2019). The researcher demonstrated the ease of learning English with the flipped learning method in technology (Yavuz & Ozdemir, 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For example, the English curriculum of 2 nd , 3 rd and 4 th grades of the primary schools is based on listening and speaking skills for which the use of technology is required; some of the teachers may have difficulty in terms of using technology. Technology is very effective in language learning (Uzunboylu & Ozcinar, 2009;Ceker & Keser, 2019;Tavoosy & Jelveh, 2019;Tajgozari, 2019). The researcher demonstrated the ease of learning English with the flipped learning method in technology (Yavuz & Ozdemir, 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This learner-centered feature combined with instant feedback meets Mayer’s (2005) segmenting and signaling principles in that people learn better from a multimedia lesson presented in user-paced segments and when cues that highlight the essential content are provided. In addition, this feature of the dialog presented with its English audio support and oral practice is similar to subtitled video, which can effectively enhance the performance of EFL learners in listening and speaking skills (Kanellopoulou, 2019; Saed et al, 2016; Tajgozari, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have shown the positive effect of movies on language learners' listening skill (e.g., Metruk, 2018;Polat & Eristi, 2019;Yiping, 2016), speaking skill (e.g., Abdolmanafi Rokni & Jannati Ataee, 2014; Okar & Shahidy, 2019;Tajgozari, 2019) and vocabulary development (e.g., Rouhani & Rabiei, 2011;Sabouri et al, 2015;Webb, 2010). Not all movies have the same effect on proficiency development.…”
Section: Related Literaturementioning
confidence: 99%